1497 Methods to diagnose carbon monoxide exposure: A scoping review. Issue 12 (22nd November 2022) - Babu, Ashik; Jarman, Heather; Moss, Phil; Reid, Stephen
Abstract : Aims, Objectives and Background: Carbon-monoxide (CO) is a colourless, odourless gas produced from incomplete combustion of carbon-containing fuels. Measurement of CO levels to diagnose exposure is difficult due to its short half-life. The effects of exposure to CO range from mild symptoms, such as headache, to neurotoxicity and death. In this scoping review we aimed to establish the existing methods used in clinical practice and research to determine CO exposure and map the diagnostic cut-off values used. Method and design: We undertook a scoping review to establish methods used in clinical practice and research to measure CO exposure and to determine diagnostic thresholds in each. EMBASE, Medline and CINAHL databases were searched for published articles in English from 2002 onwards using keywords 'carbon monoxide', 'poisoning' and 'diagnosis'. Two reviewers independently screened published abstracts for inclusion, with a third arbiter where there was lack of agreement between reviewers. Full text papers were then reviewed, and data extracted on methods used to measure CO level, diagnostic cut-off values, and whether CO exposure was from a known or unknown source. Results and Conclusion: A total of 85 papers were identified meeting the inclusion and exclusion criteria. The most common methods identified for diagnosing CO exposure were measurement of carboxyhaemoglobin (COHb) in whole blood (50.5%) and CO-oximeter spectrophotometrics (20%). Diagnostic values were poorly reported and varied in non-smokers and smokers. Exhaled CO levels using breath analysers (8.2%) and ambient CO measurement (11.7%) were also documented. Diagnostic threshold values varied between 2–5% in non-smokers and 10–15% in smokers. Several methods are used in clinical practice and research to diagnose CO exposure. There is variation in the cut-off values used to make this diagnosis which is challenging for clinicians and makes comparison of research findings difficult.